Pengaruh Massa Adsorben Dan Laju Pengadukan Terhadap Penyisihan FE, Warna Dan PH Air Gambut Secara Adsorpsi Dengan Adsorben Cangkang Buah Karet - Sesvi Bonita. B; Edward HS; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Water sources in peaty areas or swampy areas are generally shallow with brown water, high levels of humic acid, organic matter and iron. Rubber fruit shell is one of the organic wastes that has the potential to be used as an adsorbent because it contains quite a lot of lignin. This study aims to determine the effect of adsorbent mass and stirring rate in the adsorption process using rubber fruit shell adsorbents in peat water treatment. In peat water treatment the independent variables used in this study were the adsorbent mass of 5.5, 6.5 and 7.5 grams in 1000 ml and stirring speed of 90, 100, 110 and 120 rpm. The highest removal efficiency of Fe metal in peat water was 73.91%, with adsorbent mass of 6.5 grams and stirring speed of 90 rpm. The highest color removal efficiency was 64.87%, at a mass of 5.5 grams with a speed of 100 rpm, while for pH obtained a pH of 7.0, at a mass of 5.5 grams with a stirring speed of 90 rpm. The adsorption capacity for Fe metal was achieved at an adsorbent mass of 5.5 grams with a stirring speed of 120 rpm of 0.1732 mg/gr and the adsorption capacity for color was achieved at an adsorbent mass of 5.5 grams with the highest stirring speed of 100 rpm of 103.09 mg/gr. gr. The equation of the selected Fe adsorption isotherm is the Langmuir isotherm with an R2 value of 0.9998. Keywords: rubber fruit shell, Adsorption, Peat Water, Adsorption Capacity